Increasing The Students’ Vocabulary Mastery By Using Hyphonymy Game At The Eighth Grade Of SMP Negeri 1 Gunungsitoli Barat In 2022/2023 - Ester Surya Ningsih Zebua; Hasrat Sozanolo Harefa; Yasminar Amaerita Telaumbanua; Yaredi Waruwu (Departement of Mathematics Education, 2023)
Vocabulary can be defined as the total amount of words that are necessary to convey ideas and express the speaker' intent. Vocabulary is the essential thing we need to master in mastering a language. However, in reality there are many students who lack of vocabulary. Many students said that English difficult to understand. And they can’t categorize the English vocabulary also. The purpose of this research is to increase students’ vocabulary mastery by using Hyponym Game. In this research the researcher conducted Classroom Action Research (CAR) design. The subject of this research is the eighth grade students of SMP Negeri 1 Gunungsitoli Barat which consist of 26 students. This research was applied in two cycles. In Cycle I, there were 1 (4%) students who got score among 0-49 classified as “Very Poor Criteria”, 5 (19%) students got classified as “Poor Criteria”, 8 (31%) students classified as “Average Criteria”, there were 12 (46%) students classified as “Good Criteria” and no one students who reached the “Excellent Criteria”. Moreover the average of students’ mark in Cycle I was 63,46. In Cycle II, there were 14 (54%) students classified as “Excellent Criteria”, 10 (38%) students classified as “Good Criteria”, 1 (4%) students who classified as “Average Criteria”, there were 1 (4%) students classified as “Poor Criteria” and no one students who reached the “Very Poor Criteria”. The average of students’ mark was 80,19. Based on the result the researcher concluded that implementetaion of Hyphonymy game increase students’ vocabulary mastery.